Hallucination, ethnography and identity in The Three Halves of Ino Moxo by César Calvo - Dillon, Alfredo (2022)
The aim of this article is to examine how the narrator in César Calvo’s novel The Three Halves of Ino Moxo: Teachings of the Wizard of the Upper Amazon tries to portray the Amazonian culture from the inside. The analysis focuses on the narrative passages that describe the visions experienced by the characters after consuming ayahuasca. Furthermore, we study the tension between poetic prose and ethnographic register in this novel, as we explore how the Amazonian universe (with its beliefs, myths and knowledges) participates in the construction of a heterogeneous Peruvian national identity.